2012
DOI: 10.1111/j.1600-0668.2012.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sampling methods for the assessment of indoor microbial exposure

Abstract: Significant discrepancies between sampling methods regarding indoor microbial exposures have been revealed. This study thus facilitates comparison between methods and may therefore be used as a frame of reference when studying the literature or when conducting further studies on indoor microbial exposure. Results also imply that the relatively simple EDC method for the collection of settled dust may be used as an alternative to otherwise tedious and time-consuming airborne dust sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 30 publications
3
87
1
Order By: Relevance
“…Generally, there are no uniformly accepted, or validated, quantitative environmental sampling methods to assess exposure to mould and other agents associated with damp indoor environments (ACGIH, 2009;Frankel et al, 2012a). Andersen Impactor and Biotest RCS High Flow air samplers are widely used to detect and quantify bioaerosols, identify bioaerosol release from sources, assessment of human exposure to biological agents, and monitor the effectiveness of control measures (Li, 2011;Saldanha and Manno, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there are no uniformly accepted, or validated, quantitative environmental sampling methods to assess exposure to mould and other agents associated with damp indoor environments (ACGIH, 2009;Frankel et al, 2012a). Andersen Impactor and Biotest RCS High Flow air samplers are widely used to detect and quantify bioaerosols, identify bioaerosol release from sources, assessment of human exposure to biological agents, and monitor the effectiveness of control measures (Li, 2011;Saldanha and Manno, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that in environments like homes [35], university buildings [37], schools [6] and day-care centers [4], the main source of airborne bacteria indoors are humans and human activities. Bacterial exposure levels in homes are influenced by many factors, including, for example, relative humidity of indoor air and seasons during the year [22,44]. Moisture has a great influence on fungal growth and bacterial viability [59].…”
Section: Introductionmentioning
confidence: 99%
“…Airborne dust measurements from these homes have been reported in another study that compared various dust-sampling methods (7). Therefore, details regarding the choice of homes can be found elsewhere (7).…”
Section: Selection Of Homesmentioning
confidence: 99%
“…The assay has previously been used on bioaerosol samples from biofuel plants (55) and on dust samples from homes (7). It has been shown that cell activation could be related to the multifactorial composition of the bioaerosol and could thus be used as a measurement of the total inflammatory potential (TIP) of a given sample (55).…”
mentioning
confidence: 99%